A preliminary study of the aesthetic Implications of Taijiquan - Mou, Xueting; Sun, Aihua (The Journal of the International Society of Chinese Health Practices, 2021)
Objective: In order to promote the implementation of China's "Healthy China" strategy and to facilitate the expansion and development of Taijiquan in the context of the successful international inscription, this paper, in the context of aesthetics, begins with the "truth" of Taijiquan, benefits from the practitioner's physical awareness and psychological cognition, and explores the "beauty" of its meaning. "The paper explores the "beauty" of taijiquan's meaning in the context of aesthetics. The aim is to explore the beauty of Taijiquan for the benefit of the physical and mental health of mankind, and to serve the world in concert. Methods: observation method; aesthetic formal analysis; logical analysis. Results: Taijiquan has profound connotations, and this paper elaborates on its aesthetic implications at three levels, namely, the beauty of form, the beauty of divinity, and the beauty of literary meaning. Physical beauty: The beauty of form is the basis for the beauty of the spirit and the meaning of the text, and is the primary purpose of Taijiquan practice. The first is to shape the lines of the practitioner's body through practice, outlining the beautiful state of the human form. The second is the beauty of roundness and balance, of rigidity and flexibility, which is embedded in the process of Taijiquan demonstration: Taijiquan is concerned with the process of forming movements, such as left first, right first, up first, down first, up in the middle, up in the middle, up in the middle, up in the middle, round in the outside, square in the inside, etc., i.e. in the process of movement, there must be a force divided to the opposite direction, so that the force and the reverse force are in harmony with each other, and the body is always in a balanced state, and after the centre of gravity has moved, it is still in the centre, making the shape of the body. The speed of taijiquan practice requires rapidity in movement and softness in stillness, with distinct rhythms, deepening the breath in movement and showing the beauty of masculinity with swift and fierce force, while breathing slowly and evenly in stillness, with the breath sinking into the dantian and the movements rounded and loose, showing the beauty of femininity. The beauty of charm: under the influence of thousands of years of Chinese civilisation, Taijiquan is rich in philosophical and aesthetic ideas, and seeks to express the meaning of the real and the imaginary. Mencius said that "fullness is beauty, and fullness with brilliance is greatness", and that all Taijiquan stances and forms are "real". Xunzi said, "What is not complete and not pure is not enough to be beautiful." Taijiquan uses intention to bring qi and qi to bring form, and the intention and qi of each move and stance are all virtual. Take the open and closed pile as an example, when the form is open the intention is closed, when the form is closed the intention is open, in the open there is closed, in the closed there is open, inside and outside are combined, i.e. the reality and emptiness exist in each posture, and the beauty of the divine rhythm flows from each posture. Practitioners who are imbued with it pursue both internal and external cultivation in the state of mind of emptiness and reality, achieving the beauty of inner strength and subtle softness in the stances. The spirit of the outer form is invisibly displayed, the inner strength is vivid, and the beauty of divine charm is revealed in the slightest hint. The chi of taijiquan has a fitness effect, and the body is lighter with the chi, thus showing the beauty of the chi rhythm, like flowing clouds and water. With the music that blends in with the Taijiquan demonstration, under the gentle and melodious music, the Taijiquan is loose but unrelenting, tight but not rigid, containing internal energy, round and free, and the form of the gods floats, rendered in such an artistic atmosphere, one has to enjoy it, which can only be understood but not expressed. Beauty in context: First of all: Taijiquan, rooted in the soil of the long history and culture of the Chinese nation. Professor Lv Yisheng has mentioned that the roots of Chinese aesthetics must lie in ancient Chinese philosophy, and that Taijiquan is a practical health movement born out of ancient Chinese philosophy, a classic work of Chinese culture. Taijiquan therefore has a rich cultural background and is known in China as the "philosophical boxing", with a profound inner meaning, and is the bearer of the unique Chinese nationality, and has developed a unique cultural and sporting system. Therefore, as Taijiquan enters the international arena and is widely disseminated, it is also a carrier of our culture of origin, assuming the historical mission of carrying forward the traditional culture of the Chinese nation, a way to build a strong Chinese culture, a way to pass on the culture of the Chinese nation, and a powerful means to develop the cultural confidence of Chinese children. Secondly: In the "Taiji Diagram", it is argued that one movement and one stillness are the roots of each other. According to Julia Zhang, the essence of Tai Chi is Yin and Yang. This is also the ancient sages' perception of the worldview. The unity of heaven and man in Taiji, acting in accordance with nature, relaxation, rigidity and flexibility, etc., manifest the profoundness of Taiji culture. In the practice of Taijiquan, the practitioner not only pursues the beauty of the practice form, but also explores its source thought and culture, absorbs the cultural spirit of Taijiquan, pursues balance, toughness and calmness, and pays attention to the cultivation of the beauty of one's inner culture, which is an invisible part of the practice of Taijiquan that cannot be ignored. Only by integrating the cultural understanding of Taijiquan into the practice of Taijiquan can Taijiquan be truly elevated to the highest level. Finally: in 2003, the Wushu Management Centre of the General Administration requested that Taijiquan competitions need to choose the appropriate costumes and soundtrack, a harmony between music and costumes and Taiji. The yin and yang concept in Taiji, which holds that Taiji contains the harmony of reality and emptiness, rigidity and flexibility, opening and closing, lifting and lowering, symmetry, etc., is the harmony of action and movement. In the long run, the literary meaning contained in Tai Chi influences the practitioner to concentrate on the body and mind, to reflect on the reflection, to cultivate the body, to deal with the balance and harmony, which has a profound and deep significance to the inner cultivation of people and helps to build a harmonious society and a better life together. Conclusion: As a carrier of traditional Chinese culture, Taijiquan contains the beauty of form, spirit and meaning. It is important to enrich the cognition of Taijiquan's form, spirit and meaning, to build cultural confidence, to promote Chinese civilisation and to create a life of truth, goodness and beauty.